Compassion and moral inclusion as cornerstones for conservation education and coexistence. (September 2021) - Yanco, Esty; Batavia, Chelsea; Ramp, Daniel
Abstract: Although coexistence permeates conservation policy and action, increased public awareness has not necessarily translated into action despite concerted conservation education effort. To galvanize and focus prosocial behavior, education that extends compassion to an expansive moral circle of living beings may encourage values of inclusion that are critical for actualizing coexistence. We used a pre-test post-test design to characterize the set of species that mattered to 52 Australian primary school students and to evaluate how a humane education intervention that encourages moral expansiveness and compassion can impact who matters and why. Following the program, the number of species that mattered to students increased and students expanded their moral circles of inclusion as represented by norms of intrinsic value. By successfully promoting greater compassion for non-human animals, interventions like coexistence education programs, and policies that replace negative norms with those that affirm the value of all living beings, the public may develop deeper connections with other living beings and ultimately feel inspired to coexist with and protect earth's biodiversity.